Rethinking Merdeka Belajar: Toward an Ethical and Epistemic Reconstruction through Pesantren Pedagogy - Moch Najib Yuliantoro; Siti Murtiningsih; Sonjoruri Budiani Trisakti; Irfan L Sarhindi (Analisa: Journal of Social Science and Religion, 2026)
This study examines the concept of Merdeka Belajar as a contemporary educational reform in Indonesia and critically analyses its ethical and epistemic foundations through the lens of pesantren-based religious pedagogy. While existing studies largely focus on pedagogical innovation, curriculum flexibility, and digital transformation, they often overlook the deeper philosophical dimensions of knowledge and moral formation. This research employs a qualitative library-based approach using critical and comparative philosophical analysis of educational policy, Islamic epistemology, and religious pedagogy. The findings reveal that Merdeka Belajar is predominantly framed within a progressive and instrumental paradigm, emphasising autonomy, flexibility, and competence development, yet it lacks a coherent ethical and epistemic foundation. In contrast, pesantren-based education represents a systematic knowledge tradition that integrates revelation, reason, and lived experience into a unified ethical–epistemic framework. This integration enables the formation of moral subjectivity, in which knowledge is not only acquired but also embodied through ethical discipline and spiritual practice. The study argues that pesantren-based religious pedagogy provides a critical conceptual resource for reconstructing the meaning of education beyond instrumental rationality, positioning education as a process of ethical self-formation and epistemic responsibility. This research contributes to the philosophical discourse on education by integrating ethical and epistemic perspectives into contemporary educational reform.